Design and Fabrication of W-Band Waveguide Slotted Array Antenna Based on Milling Process - Hongfu Meng; Yang Chen; Wenbin Dou (International Journal of Antennas and Propagation)
A single-layer waveguide slotted array antenna is proposed for W-band applications. To eliminate the alignment errors, all structures including the radiation slots, radiation waveguides, and power divider network are realized in one layer based on the milling process, and a planar metal plate is employed to cover the bottom. For example, an 8 × 9 array is designed with 1-to-8 power divider network to validate the proposed technology. The effective radiation aperture size of the array is 24 mm × 21 mm, and the height is only 8 mm. The measured reflection coefficient of the antenna is larger than 3 GHz for S11 < −10 dB. The peak gain is 25.9 dBi, and the corresponding antenna efficiency is about 65%. All cross-polarization of the antenna array is less than −35 dB. The proposed array antenna features a simple structure, low cost, and easy implementation for W-band applications.